Multicolorimetric and fluorometric dual-modal immunosensor for histamine via enzyme-enabled metallization of gold nanorods and inner filter effect of carbon dots. (July 2022) - Luo, Shuang-Zi; Yang, Jin-Yi; Jia, Bao-Zhu; Wang, Hong; Chen, Zi-Jian; Wei, Xiao-Qun; Shen, Yu-Dong; Lei, Hong-Tao; Xu, Zhen-Lin; Luo, Lin
Abstract: Histamine (HA) is one of the key causative agents associated with allergies and food poisoning. The accurate and convenient detection of HA is highly required to avert HA toxicity and ensure food safety. Herein, a multicolorimetric and fluorometric dual-readout immunosensor for HA detection was developed based on an alkaline phosphatase (ALP) enabled multicolor change reaction and fluorescence quenching of carbon dots (CDs) resulting from the metallization of gold nanorods (Au NRs). In this immunosensor, ALP is employed as labeling enzyme which can efficiently catalyze the hydrolysis of ascorbic acid 2-phosphate into ascorbic acid (AA). Then, the resultant AA can reduce Ag + into silver monomer, and a silver shell is deposited on the surface of Au NRs to form Au/Ag core-shell nanorods (Au NRs@Ag). This leads to the blue-shift of the longitudinal local surface plasmon resonance peak of Au NRs and a vivid multicolor variation. Meanwhile, the ﬂuorescence of CDs can be gradually quenched via inner-filter effect by the resultant Au NRs@Ag. Multicolorimetric assay allows a semiquantitative detection with a visible detection limit of 0.25 mg/L, and fluorometric assay provides a sensitive and accurate quantitative detection with a detection limit of 0.08 mg/L. The immunosensor not only fulfills the reliable and accurate detection requirements but also fits different testing needs for both laboratory and on-site detection. Highlights: We developed a dual-mode sensor for rapid and accurate histamine detection in foods. Tunable metallization of gold nanorods was used for multicolorimetric sensing. Samples with excess histamine can be easily discriminated with the naked eye. A carbon dots was employed as fluorescent signal source for fluorescent sensing. The carbon dots quenching mechanism was confirmed to be inner filter effect.